Development of CompactRIO Based PID Temperature Controller - Kaur, Navneet (My University, 2009)
During the last 10 years, most of the technological advancements have occurred in the field of high volume products like mobile phones, DVD players, microwave ovens etc. New York Times stated that ―On average an American comes in contact with sixty microprocessors in a day‖. All this is possible because of the progress made in the field of embedded systems. Field Programmable Gate Array (FPGA), being the latest venture in the field of embedded electronics and the most successful configuration for embedded systems, is in great demand these days. CompactRIO, a powerful control and acquisition system introduced by National Instruments, is based upon reconfigurable FPGA technology. Apart from FPGA, it also incorporates a real-time processor for reliable stand alone applications. Now instrumentation engineers can also benefit from the FPGA technology without any knowledge of hardware description languages, because the CompactRIO systems can be developed using LabVIEW development platform. In this work, we have developed a temperature controlled chamber using the NI CompactRIO. The chamber has been fabricated using the acrylic sheets. Two 200W bulbs have been used for heating purpose and a thermocouple for temperature sensing. A small CPU fan has been used for cooling and only comes into action during emergency situation. A thermocouple input module (NI 9211) has been used to acquire data from thermocouple and a digital output module (NI 9474) has been used to drive the bulbs (via a relay card) and the fan. PID control algorithm has been used for our application and is implemented in LabVIEW.
Master of Engineering in Electronics Instrumentation and Control
Keywords: CompactRIO; PID; FPGA; Temperature Controller